The AIP model as a theoretical framework for the treatment of personality disorders with EMDR therapy - De Jongh, Ad; Hafkemeijer, Laurian; Hofman, Simon; Slotema, Karin; Hornsveld, Hellen (Frontiers in Psychiatry, 2024)
Research has shown that the impact of traumatic events and circumstances on individuals is cumulative and potentially has a wide range of harmful consequences, including negative consequences on mental health. One such consequence is the development of a personality disorder, a persistent mental condition characterized by a pronounced pattern of difficulties in impulse control, emotional regulation, cognitive functions, self-esteem, and interpersonal relationships. A wide array of studies indicates that the personal history of individuals with a personality disorder is often marked by exposure to traumatic events or other types of adverse childhood experiences (ACEs). Because existing treatments for personality disorders are usually long and costly, it is essential to continue exploring alternative and complementary interventions. Nowadays, knowledge and clinical experience in regard to personality disorders have been gained in addressing ACEs by processing memories of these events through eye movement desensitization and reprocessing (EMDR) therapy. In this paper, we present a theoretical framework for this treatment approach, based on Shapiro's Adaptive Information Processing (AIP) model, describe its current empirical basis, and provide guidance on how to formulate a useful case conceptualization that can serve as a basis for the treatment of personality disorders with EMDR therapy. This approach is illustrated with a case example.